A nanocomposite membrane composed of incorporated nano-alumina within sulfonated PVDF-co-HFP/Nafion blend as separating barrier in a single chambered microbial fuel cell. Issue 28 (1st March 2016) - Kumar, Vikash; Kumar, Piyush; Nandy, Arpita; Kundu, Patit P.
Abstract : Nano-Al2 O3 is incorporated within the blend of sulfonated PVDF- co -HFP/Nafion in varying molar ratios for the preparation of nanocomposite membranes. Abstract : Nano-Al2 O3 is incorporated within the blend of sulfonated PVDF- co -HFP/Nafion in varying molar ratios for the preparation of nanocomposite membranes. A series of tests namely, water uptake, swelling ratios, ion-exchange capacity (IEC), proton conductivity, oxygen diffusivity, etc. were conducted to analyze its capability in a microbial fuel cell (MFC). The enhanced water uptake, proton conductivity, and oxygen diffusivity results were observed with increasing nano-Al2 O3 in the membrane. The sample A5, containing 5 wt% nano-Al2 O3, exhibited superior proton conductivity over a naive SPVdF- co -HFP (∼88%) and Nafion 115 membrane (∼3.5%). In addition, this prospective membrane revealed comparable ion exchange capacity and reduced oxygen diffusivity than the corresponding Nafion 115. Furthermore, the electrical efficiency of this particular membrane was determined in single chambered MFCs as a constituent of a membrane electrode assembly. Employing mixed Firmicutes as biocatalysts, a maximum power and current density of 541.52 ± 27 mW m −2 and 1900 ± 95 mA m −2 were observed from MFC, which revealed an overall ∼48 and 11% increase over the naive SPVdF- co -HFP and Nafion 115 membrane. With a marked lowering in impedance, the results indicate the relevance of the Al2 O3 filled nanocomposite as a separating barrier in single chambered MFCs for microbial bio-energy conversion.